Analisis Kebijakan Dana Desa dalam Merespon Masalah Kemiskinan di Indonesia - Ajie Hanif Muzaqi; Djoko Susanto; M. Daimul Abror; Tri Ambulanto (Universitas Dr. Soetomo Surabaya, 2022)
This study purposes to describe the evaluation of village fund program policies in answering the problem of poverty in Indonesia between 2017-2021. To obtain data in evaluating this policy, it is obtained from holistic data consisting of the number of poor people and the Building Village Index (IDM). Meanwhile, data analysis was carried out using a descriptive method by dividing into 6 (six) large regions in Indonesia, namely Sumatra, Java & Bali, Maluku & Nusa Tenggara, Sulawesi, Kalimantan, and Papua. The results showed that for five years the village fund has increased drastically. This condition also coincides with the decline in the poverty rate of around 15% from 2017 to 2021 in Indonesia. Meanwhile, IDM status by province also shows an increase from what was originally a disadvantaged village in 2017 to a developing village in 2021. The Java & Bali region is the region that contributes the most in improving the status of IDM, be it a developing, developed or independent village. Meanwhile, Papua is the largest area in the context of underdeveloped villages in Indonesia.